Visual monitoring and optical recognition of digoxin by functionalized AuNPs and triangular AgNPs as efficient optical nano‐probes. Issue 10 (9th June 2021) - Mohammadzadeh, Arezoo; Pashazadeh‐Panahi, Paria; Hasanzadeh, Mohammad
Abstract: In this study, we presented elective, sensitive, and rapid UV‐Vis spectrophotometry and calorimetric assay for the recognition of digoxin. Therefore, cysteamine‐gold nanoparticles (Cys A‐AuNPs) in the presence of cysteine acid amine and Silver nanoparticles in the presence of tetramethyl benzidine and hydrogen peroxide (AgNPs‐TMB [3, 3′, 5, 5′‐tetramethylbenzidine]‐H2 O2 ) were synthesized and utilized as the desired probe. Finally, color variation of probes was observed in the absence and presence of digoxin. Obtained results indicate that the color of Cys A‐AuNPs changed from dark pink to light in the absence and the presence of digoxin, respectively. Also, the color of AgNPs‐TMB‐H2 O2 changed from dark blue to light blue, in the absence and the presence of digoxin, respectively. Moreover, UV‐Vis spectroscopies results indicate digoxin with a low limit of quantification of 0.125 ppm in human plasma samples which linear range was 0.125 to 11 ppm.